Odpowiedzialność odszkodowawcza Skarbu Państwo za „pomyłki sądowe” – polskie doświadczenia i rozwiązania prawne - Wiśniewska, Katarzyna (Czasopismo Prawa Karnego i Nauk Penalnych, 2020)
In recent years, Poland has seen significant legislative changes in the criminal procedure which also affected State Treasury’s liability for „judicial errors”. These amendments and the frequency with which they were introduced underscore the need for appropriate analysis on the extent to which the law currently in force ensures effective compensation. The assessment is undertaken from the perspectives of international regulations, constitutional standards, as well as practical experiences. The following paper concentrates on the liability of the State Treasury for unfair application of coercive measures in criminal proceedings.